Leveraging technology to enhance STEM Education Amidst the Covid-19 pandemic: An overview of pertinent concerns - Amunga, Jane (Technium Social Sciences Journal, 2021)
Although technology in its various forms had already permeated peoples’ lives, the closure of educational institutions worldwide due to the outbreak of the Covid-19 pandemic thrust education sectors in many countries into fraught experimentation with online learning. Many educators had to adopt pedagogical practices that were in tandem with online instruction. The pandemic had a silver lining as it opened doors to new ideas and technologies that could be leveraged to enhance STEM education. This paper adopts the desk top research approach to establish the technologies that were leverageable for STEM education during the ongoing pandemic, and to determine pertinent concerns about moving STEM education online. The study found that most institutions leveraged basic synchronous and asynchronous technologies for STEM education during the pandemic. The study also established that a few institutions were embracing sophisticated technology like Virtual Reality and Augmented Reality in enhancing STEM education. There were also institutions already training VR and VR experts to meet anticipated STEM education manpower needs. It was established that while the use of technology enhanced STEM education during the Covid-19 pandemic, it raised concerns about access, equity, quality and student engagement. To address these concerns, the study recommends that governments should invest in the provision of power in rural settings and subsidize the cost of hardware for students. For equity considerations, the disadvantaged should be prioritized in the provision of technology enablers for online STEM education and measures that safeguard them should be inbuilt in the online transition plans. Finally, where possible remote labs should be established but this is not possible, students should be allowed to take series of scheduled physical lab sessions in turns and rules of social distancing enforced. Countries should look to superior technologies for online STEM education so that any similar future occurrences do not stall practical STEM education sessions.